2020
DOI: 10.1038/s41398-020-0765-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic overlap between psychotic experiences in the community across age and with psychiatric disorders

Abstract: This study explores the degree to which genetic influences on psychotic experiences are stable across adolescence and adulthood, and their overlap with psychiatric disorders. Genome-wide association results were obtained for adolescent psychotic experiences and negative symptom traits (N = 6297-10,098), schizotypy (N = 3967-4057) and positive psychotic experiences in adulthood (N = 116,787-117,794), schizophrenia (N = 150,064), bipolar disorder (N = 41,653), and depression (N = 173,005). Linkage disequilibrium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Estimates with overlapping points are labeled for the sake of clarity. Relevant results from Barkhuizen et al 121 are not plotted, as they were not reported with standard errors in the original study, while estimates from Anttila et al 88 are excluded owing to negative standard errors being reported in the original study. A correlation matrix of all estimates is also provided in the Supplementary Material, available online.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates with overlapping points are labeled for the sake of clarity. Relevant results from Barkhuizen et al 121 are not plotted, as they were not reported with standard errors in the original study, while estimates from Anttila et al 88 are excluded owing to negative standard errors being reported in the original study. A correlation matrix of all estimates is also provided in the Supplementary Material, available online.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising given the known phenotypic association between psychotic experiences and psychiatric disorders 67 72 and could be explored further. Evidence suggests that psychotic experiences in adults have somewhat different underlying causal influences compared to psychotic experiences during adolescence 73 which may explain that lack of causal associations between smoking and psychotic experiences in later life. We also note that the GWASs on positive psychotic experiences were based on a small number of cases, which could have resulted in low power to detect causal effects in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising given the known phenotypic association between PE and psychiatric disorders (84-89) and could be explored further. Evidence suggests PE in adults have somewhat different underlying causal influences to PE during adolescence (90) and this may explain that lack of causal associations of PE in later life with smoking behaviours.…”
Section: Discussionmentioning
confidence: 99%